PROBLEMATIKA PROSES PENYELESAIAN SENGKETA TUN DENGAN MENGGUNAKAN UPAYA ADMINISTRATIF SETELAH DIBERLAKUKANNYA UU NO. 30 TAHUN 2014 - I Ketut Oka Astawa; Putu Lantika Oka Permadhi (Jurnal Hukum Saraswati (JHS), 2020)
The use of administrative efforts in a state administration dispute was originally with an unsatisfied attitude towards an act of state administration. Although in its procedure, administrative efforts do not always have to be related to the case of litigation at a court in the state administrative court.This administrative effort is also one of the legal protections from the legal actions of a state administration agency or official.The positive side of doing administrative efforts that carry out a complete assessment of a State Administration Decree both in terms of Legality and Opportunity aspects,the parties are not confronted with the outcome of a win or lose decision as in the judiciary, but with a deliberative approach.